μRTZvisor: A secure and safe real-time hypervisor - Martins, José (2017)
Virtualization has been deployed as a key enabling technology for coping with the ever growing complexity and heterogeneity of modern computing systems. However, on its own, classical virtualization is a poor match for modern endpoint embedded system requirements such as safety, security and real-time, which are our main target. Microkernel-based approaches to virtualization have been shown to bridge the gap between traditional and embedded virtualization. This notwithstanding, existent microkernel-based solutions follow a highly para-virtualized approach, which inherently requires a significant software engineering effort to adapt guest operating systems (OSes) to run as userland component s. In this paper, we present μRTZVisor as a new TrustZone-assisted hypervisor that distinguishes itself from state-of-the-art TrustZone solutions by implementing a microkernel-like architecture while following an object-oriented approach. Contrarily to existing microkernel-based solutions, μRTZVisor is able to run nearly unmodified guest OSes, while, contrarily to existing TrustZone-assisted solutions, it provides a high degree of functionality and configurability, placing strong emphasis on the real-time support. Our hypervisor was deployed and evaluated on a Xilinx Zynq-based platform. Experiments demonstrate that the hypervisor presents a small trusted computing base size (approximately 60KB), and a performance overhead of less than 2% for a 10 ms guest-switching rate.